2022
DOI: 10.1002/term.3332
|View full text |Cite
|
Sign up to set email alerts
|

Efficient engineering of human auricular cartilage through mesenchymal stem cell chaperoning

Abstract: A major challenge to the clinical translation of tissue‐engineered ear scaffolds for ear reconstruction is the limited auricular chondrocyte (hAuC) yield available from patients. Starting with a relatively small number of chondrocytes in culture results in dedifferentiation and loss of phenotype with subsequent expansion. To significantly decrease the number of chondrocytes required for human elastic cartilage engineering, we co‐cultured human mesenchymal stem cells (hMSCs) with HAuCs to promote healthy elasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Dong et al co-cultured auricular chondrocytes with human MSCs at 10/90, 25/75, and 50/50 ratios for 6 months. After several observations, it was possible to obtain structurally well maintained and healthy human elastic cartilage by this method [ 190 ]. Posniak et al chose to use a 3D bioprinting scaffold made from a combination of GelMA and methacrylic acid-hyaluronic acid.…”
Section: Main Textmentioning
confidence: 99%
“…Dong et al co-cultured auricular chondrocytes with human MSCs at 10/90, 25/75, and 50/50 ratios for 6 months. After several observations, it was possible to obtain structurally well maintained and healthy human elastic cartilage by this method [ 190 ]. Posniak et al chose to use a 3D bioprinting scaffold made from a combination of GelMA and methacrylic acid-hyaluronic acid.…”
Section: Main Textmentioning
confidence: 99%
“…Jang et al [ 17 ] demonstrated that the co-culture of adipose-derived stem cells (ASCs) with chondrocytes is beneficial to chondrogenic differentiation and cartilage regeneration through in vitro and in vivo experiments of ASCs/chondrocytes-laden 3D printed scaffolds. Dong et al [ 28 ] used collagen to encapsulate human MSCs and auricular chondrocytes, and then seeded them on 3D printed PLA scaffolds for cartilage regeneration. After 6 months of implantation, the group with 10% cell ratio of chondrocytes can still effectively generate cartilage tissue, which was not different from high ratio of chondrocytes group (50%) in volume, histologic and compressive strength.…”
Section: Traditional 3d Printed Scaffolds With Cell Seeding For Tissu...mentioning
confidence: 99%
“…Kang et al (2012); Kang et al (2013) also co-cultured BMMSCs and chondrocytes in different ratios, and finally, the study found that 30% of chondrocytes are required to generate cartilage tissue of satisfactory shape and quality at least, and the MC: BMMSC ratio of 5:5 showed the highest Young's modulus and the densest elastic fibers, which were consistent with the expression of DCN and LOXL2 genes (cartilage matrix-related genes). Nevertheless, in the study by Dong et al (2022), they co-cultured human MCs and human BMMSCs and efficiently produced wellshaped human elastic cartilage without volume loss, even when human MCs accounted for only 10% of the total number of transplanted cells. In Cohen et al (2018)'s study, they also found that BMMSCs and MCs co-cultured in a 1:1 ratio appeared as bundles of collagen fibers in the perichondrial layer, rich in proteoglycan deposits, forming an elastin fiber network similar to natural human ear cartilage, with the protein composition and mechanical stiffness of natural tissue.…”
Section: Bone Marrow Mesenchymal Stem Cellsmentioning
confidence: 99%
“…After the co-culture model treatment, the cells were attached to the PLA/PCA scaffold, and the cartilage was formed in vitro and implanted into the subcutaneous tissue of the animal. After a period of observation, the elasticity and shape of the scaffold were well-maintained ( Kang et al, 2012 ; Kang et al, 2013 ; Cheng et al, 2014 ; Zhang et al, 2014 ; Morrison et al, 2016 ; Zhao et al, 2017 ; Cohen et al, 2018 ; Dong et al, 2022 ). The results demonstrated that the co-culture model provided a high-quality strategy for auricular cartilage regeneration with significant potential for tissue-engineered auricular reconstruction.…”
Section: Stem Cell Types In Chondrogenesismentioning
confidence: 99%